The Effect of the Problem-Based Learning Model with Edpuzzle Media on the Material of Plant Body Parts on Critical Thinking Skills and Learning Outcomes of Elementary School Students - Novisulistina, Riwut; Jekti Prihati; Slamet Hariyadi (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2025)
One of the essential subjects taught in the Merdeka Curriculum is Science and Social Studies (IPAS). This subject plays a crucial role in enhancing students' thinking abilities. Consistent development of thinking skills contributes to the formation of students' critical thinking abilities. This study aims to analyze the effect of applying the Problem-Based Learning (PBL) model assisted by Edpuzzle media on the critical thinking skills and learning outcomes of elementary school students in the topic of plant body parts. The research employed a quasi-experimental method with a non-equivalent pretest-posttest control group design. The study subjects consisted of two classes: the experimental class, which implemented the PBL model using Edpuzzle, and the control class, which used conventional teaching methods. The research instruments included a critical thinking skills test (essay format) and a learning outcome test (multiple-choice format). The data were analyzed using ANCOVA. The results showed that the PBL model with Edpuzzle media had a significant effect on improving students' critical thinking skills and learning outcomes compared to conventional instruction (Sig. = 0.0001 < 0.05). These findings imply that teachers can integrate Edpuzzle-based PBL into daily lessons through interactive videos and guided problem-solving. Schools need to provide training and adequate infrastructure, while policymakers should support digital PBL integration in curriculum implementation. Future studies are encouraged to apply this model in other subjects and grade levels to examine its broader impact